2021
DOI: 10.5586/aa.7411
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Potential of Selected Essential Oils From Plants of Lamiaceae and Asteraceae Families

Abstract: Essential oils from Monarda fistulosa L., Satureja pilosa Vel., Origanum vulgare subsp. hirtum Ietswaart. (Greek oregano), Micromeria dalmatica Benth., Thymus longedentatus (Degen & Urum.) Ronniger, and Artemisa campestris L. were evaluated as inhibitors of seed germination in target plants Lolium perenne L. and Trifolium pratense L. using in vitro assays. The essential oils were applied on the seeds as aqueous solutions at concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…ey contain all the macro and micronutrients indispensable for plants and exert a positive effect on the growth of soil microorganisms, soil structure, and soil water availability (Hirzel et al, 2018). A disadvantage of organic fertilizers is their slow decomposition rate, which results in slower release of nutrients into the rhizosphere (Nikolova et al, 2021;Scagel & Lee, 2012). e results presented in Table 1 indicate a significant effect of the applied dose of the manure, regardless of its type, on common basil yields.…”
Section: Discussionmentioning
confidence: 99%
“…ey contain all the macro and micronutrients indispensable for plants and exert a positive effect on the growth of soil microorganisms, soil structure, and soil water availability (Hirzel et al, 2018). A disadvantage of organic fertilizers is their slow decomposition rate, which results in slower release of nutrients into the rhizosphere (Nikolova et al, 2021;Scagel & Lee, 2012). e results presented in Table 1 indicate a significant effect of the applied dose of the manure, regardless of its type, on common basil yields.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the weight of the plants decreased by 77% as a result of the observations made 1 month after the essential oil was applied as an aqueous solution at 3, 5 and 10 µL/mL concentrations on the super absorbent Teravet, mixed with the seeds of the target plants and planted in the field. They concluded that teravet (super-absorbent) application of essential oil is a good way of herbicidal effect in field conditions [114].…”
Section: Discussionmentioning
confidence: 99%
“…e initial step in this regard is establishing the inhibitory activity of these products on the germination of the seeds. Numerous studies have documented that essential oil from aromatic plants are potent inhibitors of seed germination and radicle elongation and have the potential as products for weed control (Jouini et al, 2020;Nikolova & Berkov, 2018;Nikolova et al, 2021;Raveau et al, 2020;Verdeguer et al, 2020;Werrie et al, 2020). Oen the yield of essential oil of some plant species is meager, and their application as bioherbicides is insufficient.…”
Section: Introductionmentioning
confidence: 99%